IMPLEMENTATION OF MEDIATION IN AN EFFORTS TO SETTLE ISLAMIC FAMILY LEGAL DISPUTES IN THE PEMATANGSIANTAR RELIGIOUS COURT - Muliadin , Muliadin; T. Riza Zarzani; Andoko, Andoko (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study examines the effectiveness of mediation in resolving Islamic family law disputes in the Pematangsiantar Religious Court. Using a qualitative approach, this study analyzes data obtained from observations, interviews, and literature studies related to mediation practices in Indonesia. The results of the study indicate that although mediation has been integrated into the judicial system through Supreme Court Regulation (Perma) No. 1 of 2016 concerning Mediation Procedures, there are still various obstacles that reduce its effectiveness. These obstacles include limited mediator skills, lack of motivation and incentives for mediators, and low public awareness of the benefits of mediation. This study also highlights the importance of training and certification for mediators to improve the quality of mediation and the need for educational campaigns to raise public awareness. The conclusion of this study emphasizes the need for a multi-faceted strategy to improve the effectiveness of mediation in religious courts, which focuses not only on legal and procedural aspects but also on increasing mediator capacity and active community participation. This study contributes to a deeper understanding of mediation as an alternative to resolving Islamic family law disputes and proposes a more holistic approach to implementing mediation in Indonesian religious courts.